The Effect of Work Conflict on Job Stress and Employee Performance - Maryani, M.; Gazali, Agus Umar (Manunggal Halim Jaya, 2024)
This study examines the relationship between work conflict, job stress, and employee performance at Denpasar Hotel Makassar. The research hypotheses posit that work conflict positively and significantly influences employee performance, whereas job stress shows a positive but non-significant effect. A quantitative, cross-sectional design was employed, involving 40 respondents from Denpasar Hotel Makassar. Data was collected through questionnaires assessing perceptions of work conflict, job stress, and performance. The analysis utilized t-tests to explore these relationships. Key findings reveal that work conflict positively and significantly impacts employee performance, indicating that effective conflict management can enhance performance. Conversely, job stress demonstrated a positive but non-significant correlation with performance, suggesting that stress, while present, does not substantially impede performance and can sometimes act as a motivator. The implications for practice emphasize the need for conflict management strategies that harness conflict as a driver of performance and stress management approaches that convert stress into eustress to optimize employee outcomes. Future research should investigate these relationships in diverse organizational settings and through longitudinal studies to understand their long-term effects.